A unified integration and component testing approach from deterministic stream X-machine specifications. (March 2016) - Ipate, Florentin; Dranidis, Dimitris
Abstract One of the great benefits of using a stream X-machine to specify a system is its associatedtesting method . Under certaindesign for test conditions, this method produces a test suite that can determine thecorrectness of theimplementation under test (IUT ), provided that the basic components of the stream X-machine model have been correctly implemented. However, such an approach implies that each component can be testedin isolation from the rest of the system. This is a limitation that, in practice, can be resolved by developing stubs and drivers. However, this adds complexity to the testing process and, furthermore, these new pieces of software can introduce faults that can invalidate the theoretical results of the aforementioned testing method. This paper extends the approach by allowing component testing to be performedin parallel with integration testing, while still guaranteeing the IUT correctness under the given design for test conditions. It also shows how the integration test suite, produced in previous publications, can be reduced.